(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The social changes taking place in Indian families and financial commitment modern standard of living, changing policies of management after nationalization, international change in banking and finance have led to increase women employment. In order to share the financial burden of the spouse as well as to raise the standard of living women started their paid employment